Antibiotic depot system with radiofrequency controlled drug release - Navrátil, Ondřej; Lizoňová, Denisa; Slonková, Karolína; Mašková, Lucie; Zadražil, Aleš; Sedmidubský, David; Štěpánek, František (Colloids and surfaces. B, Biointerfaces, 2022)
Drug depot systems have traditionally relied on the spontaneous dissolution and diffusion of drugs or prodrugs from a reservoir with constant exposure to the surrounding physiological fluids. While this is appropriate for clinical scenarios that require constant plasma concentration of the drug over time, there are also situations where multiple bursts of the drug at well-defined time intervals are preferred. This work presents a drug depot system that enables repeated on-demand release of antibiotics in precise doses, controlled by an external radiofrequency magnetic field. The remotely controlled depot system consists of composite microcapsules with a core-shell structure. The core contains micronized drug particles embedded in a low-melting hydrophobic matrix. The shell is formed by a hydrogel with immobilised magnetic nanoparticles that facilitate local heat dissipation after exposure to a radiofrequency magnetic field. When the melting point of the core material is locally exceeded, the embedded drug particles are mobilised and their surface is exposed to the external aqueous phase. It is shown that drug release can be controlled in an on/off manner by a chosen sequence and duration of radiofrequency pulses. The capacity of the depot system is shown to be significantly higher than that of purely diffusion-controlled systems containing a pre-dissolved drug. The functionality of the depot system is demonstrated in vitro for the specific case of norfloxacin acting on E. coli.
Keywords: Nanoparticles; uvolňování léčiv; Hydrogels; antibakteriální látky; Anti-Bacterial Agents; Escherichia coli; Drug Liberation; hydrogely; nanočástice